2013
DOI: 10.1038/ki.2012.383
|View full text |Cite
|
Sign up to set email alerts
|

Circulating bone morphogenetic protein-7 and transforming growth factor-β1 are better predictors of renal end points in patients with type 2 diabetes mellitus

Abstract: Albuminuria and a reduced glomerular filtration rate are conventional predictors of a future decline in kidney function in patients with type 2 diabetes mellitus. Using a nested case-control study we assessed whether circulating transforming growth factor-β1 (TGF-β1) and bone morphogenetic protein-7 (BMP-7) levels more accurately predict renal end points than the conventional markers. Cases were defined as those who developed a renal end point (doubling of serum creatinine to at least 200 μmol/l, the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 47 publications
3
50
0
Order By: Relevance
“…Such biomarkers may also be used to identify new molecular targets and focus clinical trials on participants with the highest risks of progressive disease. Examples of such biomarkers would be components of the pathways already incriminated in the pathophysiology of kidney disease (e.g., RAAS, 24 bone morphogenetic protein, [25][26][27] wingless-type mouse mammary tumour virus integration site, 28,29 Notch, 30 vascular endothelial growth factor, and protein kinase C pathways, to name a few).…”
Section: Discussionmentioning
confidence: 99%
“…Such biomarkers may also be used to identify new molecular targets and focus clinical trials on participants with the highest risks of progressive disease. Examples of such biomarkers would be components of the pathways already incriminated in the pathophysiology of kidney disease (e.g., RAAS, 24 bone morphogenetic protein, [25][26][27] wingless-type mouse mammary tumour virus integration site, 28,29 Notch, 30 vascular endothelial growth factor, and protein kinase C pathways, to name a few).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted some promising new biomarkers including plasma concentrations of TGF-β to bone morphogenetic protein-7 (BMP-7) ratio [94] and TNF receptors 1 and 2 (TNFR1 and TNFR2) [95, 96]. A number of new and important biomarkers present in the urine have also emerged.…”
Section: Resultsmentioning
confidence: 99%
“…Wong et al demonstrated that decreases in circulating BMP-7 are predictive of ESRD in patients with diabetes. The prognostic value of BMP-7 was increased beyond that of the best available risk markers for diabetic nephropathy when combined with the detection of increased TGF-β levels (Wong et al, 2013). Using an analogous approach, Neuwirt et al (2014) found that a biomarker panel containing BMP-7 accurately predicts the loss of kidney function in patients with proteinuric diseases.…”
Section: Clinical Implications For Bmp-7 In Patients With Ckdmentioning
confidence: 97%